ANALYSIS OF KUR CLAIM GUARANTEE PROCEDURE EFFECTIVENESS AT PT JAMKRINDO PAMEKASAN BRANCH - Alvina, Iqlila; Wilfiya, Nukma; Munawwarah, Siti; Fatun, Fatun (Ngejha, 2024)
This study aims to analyze the procedure for guaranteeing claims for People's Business Credit (KUR) and the effectiveness of its implementation in PT. Jamkrindo Pamekasan Branch in supporting the smooth financing of micro businesses. KUR is one of the important instruments in supporting economic growth, especially for micro, small, and medium enterprises (MSMEs). As a guarantor institution, PT. Jamkrindo has a crucial role in ensuring that credit risk can be minimized so that financial institutions are more confident in distributing KUR. This study uses a descriptive approach. Qualitative if with case study methods. Data were collected through interviews, observations, and documentation studies related to the claims procedure and the implementation of the guarantee. The results of the study show that the KUR claim guarantee procedure at PT.  Jamkrindo Pamekasan Branch has been running well, although there are several obstacles in terms of coordination with distributing financial institutions. The effective implementation of this procedure has proven to support the smooth financing of micro-enterprises, but improvements are still needed in terms of the speed of the claims process and increased socialization to partners. Thus, imalization in procedures and implementation can further strengthen the role of PT. Jamkrindo in supporting the growth of MSMEs.